La autoevaluación y acreditación universitaria en la carrera profesional de la escuela de administración en la universidad "césar vallejo" de piura - Nuñez Campos, Carmen Rosa (2009)
the present investigation proposes a autoevaluation model and university accreditation in order to improve the academic quality and to make decisions in the academic processes and administrative, to obtain this is taken as study the Schools Academic Professional from Administration of the Department of Piura and as Cesar shows to the School of Pre degree of Administration of The University “Vallejo” of Piura. The used method was descriptive - the Explanatory one, using the Interviews, Surveys and consults to experts in accreditation and university autoevaluation. The results found in the institutional project define the general mission and strategies for their medium fulfillment in goals and objectives to and long term; in the academic community, I ooze main of the Professional Academic School are educational and the students actors of the educative process, for this settled down the standards of autoevaluation and accreditation of the professional race of the Academic School of The University “Cesar Vallejo” of Piura, the one that allowed to assure the academic quality in the professional academic formation, in the education processes learning, investigation, university extension and social projection, as well as the administrative, financial management and of resources of this Professional School, also that from them of the continuous improvement of the professional formation of the individual that takes it to become film star of sustainable development of the society